Human resource planning in manufacturing enterprises - Lekiqi, Bislim (Technium Social Sciences Journal, 2022)
Enterprises in Kosovo are marking significant development steps by launching quality products and services in the national, regional and international market. In this context, the role and importance of human resources is indisputable, and with it their planning. Reaching international agreements, certification of enterprises with quality standards and increasing purchasing power in Kosovo, is influencing Kosovar enterprises to produce more and more for the domestic market, but also for the international market by increasing exports. The growth trend of Kosovar manufacturing enterprises is positive and based on the current situation, this research conducted through the survey aims to bring information about human resource planning in manufacturing enterprises in Kosovo as an instrument to achieve their goals for next year, but also for the future in general. The results of this research will be able to serve enterprise managers, state decision makers and educational institutions to deepen cooperation with businesses for even deeper research that will serve you for the design of study curricula as well as for the development policies of enterprises and institutions for the future.